Effects of high temperature applied to CuAlTa alloy in air atmosphere on thermodynamic parameters and microstructure - Ercan, Ercan; Dagdelen, Fethi (Gazi Univ, Fac Engineering Architecture, 2022)
The effects of four different oxidation processes on the oxidation behavior, phase components, microstructural properties and thermodynamic parameters of a Cu-9Al-5Ta (% wt) high temperature shape memory alloy (HTSMA) were investigated through DTA/TG, XRD, SEM-EDX and DSC analysis measurements. The oxidation processes were performed at different temperatures, including 700 degrees C, 800 degrees C, 900 degrees C, and 1000 degrees C, and it is found that the surface oxidation reached saturation after 900 degrees C, and thus the oxidation constant did not increase. After oxidation, various phases, such as alpha(9R), beta(1)'(18R), gamma(1)'(2H), gamma(2)(Cu9Al4) and Ta2Al3 phases, were determined that their intensity varied with changing temperature. However, the fact that alpha(9R) and Ta2Al3 phases, which are rich in the amount of Ta elements, are difficult to diffuse with oxygen caused these phase intensity to be high. It was observed that surface oxide layers formed with increasing temperature caused to grow and expand the martensite and alpha(9R) phases. Additionally, the change in the steady-state of the alpha(9R) phase with increasing temperature also caused local changes in the chemical composition. It was observed that these expanding phases forced the oxide layer and formed oxide structures in the form of swelling and splitting on the surface. The DSC analysis showed that the martensite transformation temperature range and thermodynamic parameters do not affect the presence of martensite transformations, although they show small changes with oxidation. However, the elastic energies exhibited irregular behavior due to the heat energy transferred to the alloy. The change in phase structures with increasing oxidation changed the crystallite size.
CuAlTa alasimina hava atmosferinde uygulanan yüksek sicakli?in termodinamik parametrelerine ve mikro yapisina etkileri
Keywords: High temperature; oxidation; crystallite size; martensite phase; microstructure